Biogeographic, historical and environmental influences on the taxonomic and functional structure of Atlantic reef fish assemblages. Issue 11 (7th October 2013) - Bender, Mariana G.; Pie, Marcio R.; Rezende, Enrico L.; Mouillot, David; Floeter, Sergio R.
Abstract: Aim: To disentangle how historic, biogeographic and environmental factors have shaped the composition of different reef fish assemblages, we analysed assemblage structure from a taxonomic (proportions of species from different families) and functional perspective (diet and body size). Location: Atlantic Ocean. Methods: The distributions of 1629 fish species were compiled for 31 locations across the Atlantic Ocean (39°66′ N, 27°50′ S). These locations provide a richness gradient ranging from 54 species in St Paul's Rocks to 474 in Cuba. We used cluster analyses to assess how historical and biogeographic factors have shaped the taxonomic and functional structure (i.e. the distribution of species within families, diet and body size groups) of assemblages. We then employed a constrained analysis of principal coordinates (CAP) to test the relative influence of the distance from the biodiversity centre in the Atlantic, sea surface temperature, isolation, coral species richness and area, and coastal length on the observed patterns of assemblage structure. Results: The taxonomic and functional structure of reef fish assemblages across the Atlantic exhibits a biogeographic fingerprint, with a marked discrimination between species‐rich biogenic reefs (concentrated primarily in the Caribbean and composed of small species feeding on invertebrates) and poorer peripheral regions dominated by larger species with more diverse diets. The first CAP axis explains 87% of body size distribution in assemblages, showing that the effects of sea surface temperature and coral richness and those of isolation are antagonistic and can be embedded into a single dimension. Environmental factors, such as temperature and habitat complexity, explain the disproportionate number of small species in the Caribbean, whereas in the remaining regions the predominance of large‐bodied fish increases with isolation due to high dispersal ability. Main conclusions: We found that historical events, which have shaped the biogeography of reef fishes, and environmental characteristics (coral reefs versus periphery) have both played a role in structuring the taxonomic and functional components of Atlantic fish assemblages.